2019
DOI: 10.1186/s13000-019-0810-8
|View full text |Cite
|
Sign up to set email alerts
|

SNW1 is a prognostic biomarker in prostate cancer

Abstract: Background SNW1 is a nuclear receptor co-activator involved in splicing and transcription control, including androgen receptor signaling. Overexpression of SNW1 has been linked to adverse prognosis in different cancer types, but studies on the role of SNW1 in prostate cancer are lacking. Methods Using immunohistochemistry, we analyzed SNW1 expression in 10,310 prostate cancers in a tissue microarray (TMA) with attached clinical and molecular data. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(49 reference statements)
0
7
0
1
Order By: Relevance
“…In pitB, there was low expression of CALR (calreticulin) and reduced expression of this gene is known to favour an oncogenic phenotype [ 55 , 56 ]. In addition, there was increased expression of several genes known to be overexpressed in various cancers, including: SNW1 (SNW domain containing 1) [ 57 ], CRABP2 (cellular retinoic acid binding protein 2) [ 58 ], and CYP26A1 (cytochrome P450 family 26 subfamily A member 1) [ 59 ]. What roles these genes might play in other DICER1‐related tumours remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In pitB, there was low expression of CALR (calreticulin) and reduced expression of this gene is known to favour an oncogenic phenotype [ 55 , 56 ]. In addition, there was increased expression of several genes known to be overexpressed in various cancers, including: SNW1 (SNW domain containing 1) [ 57 ], CRABP2 (cellular retinoic acid binding protein 2) [ 58 ], and CYP26A1 (cytochrome P450 family 26 subfamily A member 1) [ 59 ]. What roles these genes might play in other DICER1‐related tumours remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This is not only demonstrated by the independent prognostic value of ANO7 staining in all applied models but also by its retained prognostic impact in cancers with comparable traditional or quantitative Gleason grade. In our patient cohort, where Gleason grading has been very thoroughly performed, most prognostic molecular parameters lose their prognostic role in cancers with homogeneous morphology 27 29 . A strong prognostic role of ANO7 loss in PCa is also in line with earlier data from Mohsenzadegan et al 7 , 26 who reported an inverse correlation between ANO7 staining intensity and tumor stage or Gleason score.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TF ESF1 could not only upregulate target gene TMPRSS2, known as the fusion gene, via the upregulation of TF SNW1 but also specifically upregulate miRNA MIR193A in the signaling pathway of lean PCa (see Figure 2). The overexpression of TF SNW1 participates in androgen receptor splicing and transcription control, and is regarded as a co-activator of nuclear receptors [29]. Finally, influenced by the above effects, the target gene TMPRSS2, expressing a type of transmembrane protein, is overexpressed, resulting in the carcinogenic mechanism.…”
Section: The Common Carcinogenic Molecular Mechanism Between Lean and Obese Pcamentioning
confidence: 99%